Proteomic analysis of venom variability and ontogeny across the arboreal palm-pitvipers (genus Bothriechis) - Pla Ferrer, Davinia (2017)
Bothriechis is a genus of eleven currently recognized slender and arboreal venomous snakes, commonly called palm-pitvipers that range from southern Mexico to northern South America. Despite dietary studies suggesting that palm-pitvipers are generalists with an ontogenetic shift toward endothermic prey, venom proteomic analyses have revealed remarkable divergence between the venoms of the Costa Rican species, B. lateralis, B. schlegelii, B. supraciliaris, and B. nigroviridis. To achieve a more complete picture of the venomic landscape across Bothriechis, the venom proteomes of biodiversity of the northern Middle American highland palm-pitvipers, B. thalassinus, B. aurifer, andB. bicolor fromGuatemala, B. marchi fromHonduras, and neonate Costa Rican B. lateralis and B. schlegelii, were investigated. B. thalassinus and B. aurifer venoms are comprised by similar toxin arsenals dominated by SVMPs (33–39% of the venom proteome), CTLs (11–16%), BPP-like molecules (10–13%), and CRISPs (5–10%), and are characterized by the absence of PLA2 proteins. Conversely, the predominant (35%) components of B. bicolor are D49-PLA2 molecules. The venom proteome of B. marchi is similar to B. aurifer and B. thalassinus in that it is rich in SVMPs and BPPs, but also contains appreciable amounts (14.3%) of PLA2s. The major toxin family found in the venoms of both neonate B. lateralis and B. schlegelii, is serine proteinase (SVSP), comprising about 20% of their toxin arsenals. The venomof neonate B. schlegelii is the only palm-pitviper venom where relative high amounts of Kunitz-type (6.3%) and γPLA2 (5.2%) inhibitors have been identified. Despite notable differences between their proteomes, neonate venoms are more similar to each other than to adults of their respective species. However, the ontogenetic changes taking place in the venom of B. lateralis strongly differ from those that occur in the venom of B. schlegelii. Thus, the ontogenetic change in B. lateralis produces a SVMP-rich venom, whereas in B. schlegelii the age-dependent compositional shift generates a PLA2-rich venom. Overall, genus-wide venomics illustrate the high evolvability of palm-pitviper venoms. The integration of the pattern of venom variation across Bothriechis into a phylogenetic and biogeographic framework may lay the foundation for assessing, in future studies, the evolutionary path that led to the present-day variability of the venoms of palm-pitvipers.